Hyaluronic acid: Function and location in the urothelial barrier for bladder pain syndrome/interstitial cystitis, an in vitro study. - Charlotte J van Ginkel; Cléo D M Baars; Dorien M Tiemessen; Cornelius F J Jansen; Frank M J Martens; Jack A Schalken; Dick A W Janssen (PLoS ONE)
Disruption of the glycosaminoglycan (GAG)-layer and urothelial barrier is an important aspect of the pathophysiology of bladder pain syndrome/ interstitial cystitis. Intravesical hyaluronic acid (HA) is often used in treatments for IC/BPS, however the role in the urothelial barrier is unknown. This study aims to clarify the location and functional contribution of HA in the urothelium, using an in vitro model. Immunohistochemistry was performed on human and porcine biopsies and on porcine cell cultures to evaluate the location of HA. Functional contribution was assessed through transepithelial electrical resistance measurements and the effects on gene expression in a differentiated primary porcine urothelial cell model. HA was found throughout in the urothelium and most abundant around the basal layer. Digestion of HA increased impermeability of the urothelium, contrasting with the effect of protamine sulfate (PS). After HA digestion, quantitative PCR analysis revealed upregulation of HA-synthesizing gene (HAS3) and the inflammatory marker (IL8). Treatment with HA and/or chondroitin sulfate therapy in undamaged cells upregulated genes related to GAG synthesis, barrier markers and inflammation. In PS-damaged cells, GAG therapy only upregulated genes associated with HA synthesis and inflammation, without affecting barrier recovery speed. These results emphasize the interaction of HA on urothelial cell inflammation and barrier repair physiology. HA seems to not directly restore the urothelial luminal GAG layer but influences barrier integrity through its interactions with urothelial cells.